2013
DOI: 10.1016/j.ophtha.2013.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Donor Age and Factors Related to Endothelial Cell Loss 10 Years after Penetrating Keratoplasty

Abstract: Objective To examine the effect of donor age and other perioperative factors on long term endothelial cell loss after penetrating keratoplasty (PKP) Design Multi-center, prospective, double-masked clinical trial Participants 176 participants from the Cornea Donor Study cohort who had not experienced graft failure 10 or more years after PKP for a moderate risk condition (principally Fuchs’ dystrophy or pseudophakic/aphakic corneal edema) Methods Corneas from donors 12 to 75 years old were assigned to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 32 publications
(45 reference statements)
3
74
0
Order By: Relevance
“…1 Expressed as endothelial cell density (ECD), one can predict the survival time of a given corneal graft, especially when planning an intraocular surgery. Studies focusing on specular microscopy results after penetrating keratoplasty (PKP) in adults [2][3][4] with Fuchs endothelial dystrophy and pseudophakic/aphakic corneal edema have shown a gradual endothelial cell loss (ECL) over time. The reported median ECL in the first 5 2 and 10 3,4 years after a successful PKP were 70% [interquartile range (IQR), 50%-77%] and 76% (IQR, 70%-82%), respectively.…”
mentioning
confidence: 99%
“…1 Expressed as endothelial cell density (ECD), one can predict the survival time of a given corneal graft, especially when planning an intraocular surgery. Studies focusing on specular microscopy results after penetrating keratoplasty (PKP) in adults [2][3][4] with Fuchs endothelial dystrophy and pseudophakic/aphakic corneal edema have shown a gradual endothelial cell loss (ECL) over time. The reported median ECL in the first 5 2 and 10 3,4 years after a successful PKP were 70% [interquartile range (IQR), 50%-77%] and 76% (IQR, 70%-82%), respectively.…”
mentioning
confidence: 99%
“…Corona sign during chronic progression of graft endothelial dysfunction after PKP After PKP, the number of corneal endothelial cells in the corneal graft decreased over the long term [21]. The exacerbated corneal edema after PKP was seen during slitlamp examination; peripheral corneal edema as a corona sign in graft and/or host cornea was seen in 18 (grades 1 and 2) of 31 PKP cases (58.1 %) and increased in size in association with progression of corneal endothelial dysfunction in the PKP graft.…”
Section: Resultsmentioning
confidence: 99%
“…Postoperative higher ECD values were significantly associated with higher baseline ECD and younger donor age in one study [34]. When the follow-up period was extended to 10 years, the study group observed that the donor age influenced ECD, although this finding was primarily influenced by a small group of the youngest donors (12 to < 34 years of age) that had the least cell loss and the best graft survival [34]. Lass et al [10] observed that younger age and female gender of the donor had a significant correlation with higher ECD over time.…”
Section: Effect Of Donor and Eye-bank Variables On Clinical Outcomesmentioning
confidence: 86%
“…Parekh et al [19] reported postmortem interval ≥ 10 hours tends to have a higher percentage of endothelial cell loss than < 10 hours of interval at both 1 year and 3 years postoperatively. Postoperative higher ECD values were significantly associated with higher baseline ECD and younger donor age in one study [34]. When the follow-up period was extended to 10 years, the study group observed that the donor age influenced ECD, although this finding was primarily influenced by a small group of the youngest donors (12 to < 34 years of age) that had the least cell loss and the best graft survival [34].…”
Section: Effect Of Donor and Eye-bank Variables On Clinical Outcomesmentioning
confidence: 91%
See 1 more Smart Citation